Analisis Kebutuhan Lahan Dan Sarana Prasarana Pengelolaan Sampah (Studi Kasus : TPA Ngegong Kota Blitar) - Mitha Aulia Hayuningrat; Erina Rahmadyanti (Jurnal Teknik Sipil, 2021)
The existence of waste is still a problem that affects almost all regions in Indonesia. Leachate is a liquid produced from the decomposition of waste in landfills which can seep into the ground and can contaminate groundwater and its surroundings. Until now, waste management, such as recycling waste or directly dumping it into a landfill, can be done using the Landfill method (landfilling) or an incinerator (incineration) is still needed to solve the waste problem. This discussion is to examine the impact of leachate channels on the environment, leachate management systems and land requirements. This study was conducted at the location of the Kenep Final Disposal Site in Pasuruan Regency. Therefore, efforts to manage existing leachate water are needed before discharge to a receiving water body or river. In this discussion, the leachate discharge value of 0,689 lt/dt was obtained so that the results for the dimensions of the Leachate Management Installation were obtained for the Stabilization Pool area 85.04 m², depth of 3.5 m, long 10 m, wide 8.5 m, and an efficiency of 67%. The Facultative pool area 198.43 m², depth of 3 m, long 15 m, wide 13.23 m, and an efficiency of 50%. The Maturation Pool area 198.43 m², depth of 3 m, long 15 m, wide 13.23 m and an efficiency of 50%. And it takes a widening of the area for the Kenep Final Disposal Site in Pasuruan Regency by 0.6 hectares or 6000 m².